Association between dietary antioxidant levels and chronic obstructive pulmonary disease: a mediation analysis of inflammatory factors - Liu, Ziyi; Li, Jiyuan; Chen, Tuotuo; Zhao, Xue; Chen, Qing; Xiao, Lihua; Peng, Zhenyu; Zhang, Hongliang (Frontiers in Immunology, 2024)
The development of chronic obstructive pulmonary disease (COPD) is strongly associated with oxidative stress, but it is unclear whether increasing dietary antioxidant intake reduces the risk of COPD. Therefore, this study assessed the association between antioxidant intake and COPD in US adults aged ≥ 40 years and further examined the correlation using the Composite Dietary Antioxidant Index (CDAI).The study included 8,257 US adults aged ≥ 40 years using data from the National Health and Nutrition Examination Survey (NHANES) for three cycles from 2007-2012. Multivariate logistic regression models were used to calculate the correlation between antioxidant intake and CDAI with COPD. Restricted cubic spline was further used to explore the exposure-response relationship.Mediation analysis was used to explore the role of inflammatory factors in the association between CDAI and COPD.Results: This study included 8257 participants (4111 women [weighted, 50.7%]; mean [SD] age, 58.8 [11.2] years). In a multivariable-adjusted model of single antioxidant intake, a linear downward association between carotenoid intake and the incidence of COPD (P for trend = 0.052; Pnon-linear = 0.961). In a multivariable adjusted model for CDAI, this association is similarly present (P for trend = 0.018; Pnon-linear = 0.360). Multiple linear regression modeling showed that leukocytes (P = Therefore, this study assessed the relationship between antioxidant intake and COPD in adults ≥40 years of age in the United States, and comprehensively evaluated the correlation between the two by means of the Composite Dietary Antioxidant Index (CDAI).